MARINE ECOTOURISM DEVELOPMENT STRATEGY OF TORAN ISLAND TOURISM AREA OF PIEH AND SEA ISLAND WATERS AROUND WEST SUMATERA PROVINCE - Irvan Dwi Putra; Joko Samiaji; Afrizal Tanjung (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was carried out in March 2019 on Toran Island, TWP Pieh Island and the Sea in the Surrounding West Sumatra Province. The purpose of this study was to determine the potential of marine ecotourism on Toran Island and its development strategy. The method used in this study is a survey method and the determination of sampling points using purposive sampling method. Data collected includes respondents' opinions, identification of ecotourism activities and measurement of water quality. The results of this study indicate that Toran Island has the appropriate potential to be developed as a marine ecotourism area. The results of the calculation of the land suitability index value for the recreational tourism beach category are at an average value of 85.2%. This value indicates that Toran Island is very suitable to be used as a marine ecotourism destination. The results of the SWOT analysis show several alternative management strategies that are appropriate for the development of marine ecotourism on Toran Island, namely: 1). Developing tourist objects and attractions by increasing facilities and infrastructure as well as tourist attractions with the quality and quantity of tourist objects that are more attractive and provide a distinctive charm for tourists. In this case the Toran Island attraction presents a tourist attraction in the form of the natural charm of the beach with white sand. 2). Developing a partnership between the local community and the government in terms of developing tourism facilities and businesses at the Toran Island tourist site. 3). Expanding promotion and marketing of Toran Island tourism objects from various local, regional, national and international market segments with a variety of promotional facilities and optimal tourism services. Keyword: Potential, Marine Ecotourism, SWOT Analysis, Toran Island